Reproductive State Modulates Retinal Sensitivity to Light in Female Túngara Frogs - Leslie, Caitlin E.; Rosencrans, Robert F.; Walkowski, Whitney; Gordon, William C.; Bazan, Nicolas G.; Ryan, Michael J.; Farris, Hamilton E. (Frontiers in Behavioral Neuroscience, 2020)
Visual cues are often a vital part of animal communication and courtship. While a plethora of studies have focused on the role that hormones play in acoustic communication of anurans, relatively few have explored hormonal modulation of vision in these animals. Much of what we do know comes from behavioral studies, which show that a frog's hormonal state can significantly affect both its visual behavior and mating decisions. However, to fully understand how frogs use visual cues to make these mating decisions, we must first understand how their visual system processes these cues, and how hormones affect these processes. To do this, we performed electroretinograms (ERGs) to measure retinal sensitivity of túngara frogs (Engystomops pustulosus), a neotropical species whose mating behavior includes previously described visual cues. To determine the effect of hormonal state on visual sensitivity, ERGs were recorded under scotopic and photopic conditions in frogs that were either non-reproductive or hormone-treated with human chorionic gonadotropin (hCG) prior to testing. Additionally, measurements of optical anatomy determined how túngara frog eye and retina morphology related to physiological sensitivity. As expected, we found that both sexes display higher visual sensitivity under scotopic conditions compared to photopic conditions. However, hormone injections significantly increased retinal sensitivity of females under scotopic conditions. These results support the hypothesis that hormonal modulation of neural mechanisms, such as those mediating visually guided reproductive behavior in this species, include modulation of the receptor organ: the retina. Thus, our data serve as a starting point for elucidating the mechanism of hormonal modulation of visual sensitivity.